The Lemkos of Poland: Articles and Essays - Best, Paul J.; Moklak, Jarosław (Carpatho-Slavic Studies Group and the Historia Iagellonica Press, 2000)
Keywords: Ethnic relations; History; Poland; Lemky; Poland; dept.psc; faculty_collection

The Aegean Sea After the Cold War: Security and Law of the Sea Issues - Chircop, Aldo E.; Gerolymatos, André; Iatrides, John O. (International political economy series, 2000)
Keywords: Aegean Sea Region; Security, International; Greece; Foreign relations; Greece; Law of the sea; Turkey; Turkey; dept.psc; faculty_collection

Realignment and Party Revival: Understanding American Electoral Politics at the Turn of the Twenty-First Century - Paulson, Arthur C. (Praeger, 2000)
Keywords: Election; Political parties; Presidents; United States; dept.psc; faculty_collection

Affirmative Action and the University Race, Ethnicity, and Gender in Higher Education Employment - Rai, Kul B.; Critzer, John W. (University of Nebraska Press, 2000)
Affirmative Action and the University is the only full-length study to examine the impact of affirmative action on all higher education hiring practices. Drawing on data provided by the Equal Employment Opportunity Commission and the U.S. Department of Education's National Center for Education Statistics, the authors summarize, track, and evaluate changes in the gender and ethnic makeup of academic and nonacademic employees at private and public colleges and universities from the late 1970s through the mid-1990s. Separate chapters assess changes in employment opportunities for white women, blacks, Asians, Hispanics, and Native Americans. The authors look at the extent to which a two-tier employment system exists. In such a system minorities and women are more likely to make their greatest gains in non-elite positions rather than in faculty and administrative positions. The authors also examine differences in hiring practices between public and private colleges and universities. Kul B. Rai is a professor of political science at Southern Connecticut State University. His works include "America in the Twenty-First Century: Challenges and Opportunities in Domestic Politics". John W. Critzer is a professor of political science at Southern Connecticut State University., "Affirmative Action and the University is the only full-length study to examine the impact of affirmative action on all higher education hiring practices. Drawing on data provided by the Equal Employment Opportunity Commission and the U.S. Department of Education's National Center for Education Statistics, the authors summarize, track, and evaluate changes in the gender and ethnic makeup of academic and non-academic employees at private and public colleges and universities from the late 1970s through the mid-1990s. Separate chapters assess changes in employment opportunities for white women, blacks Asian, Hispanics, and Native Americans." "The authors look at the extent to which a two-tier employment system exists. In such a system minorities and women are more likely to make their greatest gains in non elite positions rather than in faculty and administrative positions. The authors also examine differences in hiring practices between public and private colleges and universities."--Jacket.
Keywords: Discrimination in higher education; Employment; United States; United States; Affirmative action programs; United States; Minority college administrators; United States; Minority college teachers; dept.psc; faculty_collection

Conclusion: The Aegean — Life-line and Battle-line - Chircop, Aldo; Gerolymatos, André; Iatrides, John O. (The Aegean Sea after the Cold War: Security and Law of the Sea Issues, 2000)
From the dawn of the Bronze Age and Homer’s immortal epics to the latest confrontation in the Middle East and the Persian Gulf, the Aegean Sea has been critically important to countless armies of merchants, warriors, and crusaders. As a geographic entity, it is a narrow body of water dotted with islands, islets, and rocks. However, the Aegean is both a link and barrier between the Mediterranean and Black Seas, and the maritime causeway between the land masses of Europe, Asia, the Near East, and Africa. In effect, this maritime highway has been one of history’s more productive crucibles for human accomplishment, as well as an arena of conflict and destruction.
Keywords: Geographic Entity; Greek Settlement; Narrow Body; Productive Crucible; Turkish Strait; dept.psc